Pulmonary microbiota signatures adjacent to adenocarcinoma, squamous cell carcinoma and benign lesion - Li, Jinyou; Wu, Gang; Yang, Ju; Yan, Jiai; Li, Dan; Wang, Qinyue; Xia, Yanping; Zhu, Jie; Guo, Baoliang; Cheng, Fengyue; Sun, Jing; Cao, Hong; et al. (Frontiers in Oncology, 2023)
The occurrence and progression of lung cancer are influenced by pulmonary microbiota, yet the relationship between changes in the pulmonary microbiota and lung cancer remains unclear. To investigate the correlation between pulmonary microbiota and the signature of lung lesions, we analyzed the microbial composition at sites adjacent to the stage 1 adenocarcinoma, squamous carcinoma and benign lesion tissues in 49 patients by using 16S ribosomal RNA gene sequencing. We then conducted Linear discriminant analysis, receiver operating characteristic (ROC) curve analysis and PICRUSt prediction based on 16S sequencing results. Overall, the microbiota composition at sites close to lung lesions showed significant differences between different lesion types. Based on the results of LEfSe analysis, Ralstonia, Acinetobacter and Microbacterium are the dominant genera of lung adenocarcinoma (LUAD), lung squamous carcinoma (LUSC) and benign lesions (BENL), respectively. Furthermore, we determined the diagnostic value of the abundance ratio of Ralstonia to Acinetobacter in adenocarcinoma patients through ROC curve analysis. The PICRUSt analysis revealed 15 remarkably different metabolic pathways in these lesion types. In LUAD patients, the increase of the pathway associated with xenobiotic biodegradation may be due to the continuous proliferation of microbe with degradation ability of xenobiotics, which implied that LUAD patients are often exposed to harmful environment. The abundance of Ralstonia was related to the development of lung cancer. By measuring the abundance of microbiota in diseased tissues, we can distinguish between different types of lesions. The differences in pulmonary microbiota between lesion types are significant in understanding the occurrence and development of lung lesions.